Methods of using interactive methods in preschool educational organizations, conducting music classes - Ravshan Rakhimov Naimovich (Genius Journals, 2022)
This article provides information on methods of using interactive methods in preschool educational organizations, conducting music classes.
Keywords: preschool; institutions; teaching; pedagogy